Review of Endovenous Thermal Ablation of the Great Saphenous Vein: Endovenous Laser Therapy Versus Radiofrequency Ablation. Issue 5 (May 2018) - Ahadiat, Omeed; Higgins, Shauna; Ly, Alexandre; Nazemi, Azadeh; Wysong, Ashley
Abstract : BACKGROUND: Endovenous thermal ablation is a popular treatment for varicose veins of the greater saphenous vein. Two common techniques of thermal ablation are endovenous laser therapy (EVLT) and radiofrequency ablation (RFA). OBJECTIVE: The authors compare EVLT and RFA in vein therapy. METHODS: A review was conducted using PubMed. Studies comparing the treatment modalities were gathered and compared on the basis of 5 main standpoints, including: efficacy, side effects, serious complications, recurrence, and quality of life. RESULTS: It was found that EVLT and RFA are both highly efficacious (>80%). Endovenous laser therapy seems to be slightly more efficacious than RFA in numerous studies but its significance is uncertain. Side effect profiles varied regarding postoperative pain and bruising because both were seen to be significantly less using RFA. Serious complications were found to be rare in both with no significant difference in incidence. Recanalization rate was observed to be higher using RFA with uncertainty in significance among various studies. Quality of life improved after both procedures with no significant difference among the 2. CONCLUSION: Efficacy and recurrence rate seem to favor EVLT, whereas postoperative pain and bruising favor RFA. Further studies are needed to validate the significance of the differences found.